PENGEMBANGAN SUMBER DAYA BUMDES ASUNG DAYA DALAM ADMINISTRASI KEUANGAN BERBASIS KOMPUTER - Nurdian Susilowati; Indah Anisykurlillah; Amir Mahmud (LP2M Universitas Hasanuddin, 2021)
This community service applied information technology in the form of a simple accounting system application using a spreadsheet (general ledger) for Village-Owned Enterprises (BUMDes). This activity aims first to understand the recording of financial transactions using the Financial Accounting Standards for Entities without Public Accountability (SAK ETAP). Second, compiling financial reports utilizing a general ledger using a computer spreadsheet system. The service methods used are socialization, training, and mentoring. Activities are packaged in the form of lectures that are delivered virtually using zoom meetings and Whats up Group (WAG). The target audience is the BUMDes management and director, as well as the Jatijajar Village apparatus. The first step taken is training to input transaction data on general journal sheets. Second, the practice of recording and posting to general and auxiliary ledgers to produce financial reports. The activity results were that the Directors and management of BUMDes understood and began to get acquainted with recording financial transactions using SAK ETAP. Besides, it is also familiar with mathematical function formulas in Excel to compile general ledger accounting spreadsheets. This general ledger makes it easier to record accounting and prepare financial reports that are tailored to the needs of BUMDes. If the BUMDes is in the form of a trading company, will prepare the trading company financial report. Examples are minimarkets and grocery stores owned by BUMDes. Meanwhile, if the company is a service company, a service company financial report is prepared according to the type of service being performed. Such as water management services, waste management services, and others. — Kegiatan pengabdian ini menerapkan teknologi informasi berupa aplikasi sistem akuntansi sederhana menggunakan spreadsheet (general ledger) untuk Badan Usaha Milik Desa (BUMDes). Tujuan kegiatan ini adalah pertama, melakukan pemahaman pencatatan transaksi keuangan menggunakan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP). Kedua, menyusun laporan keuangan menggunakan general ledger menggunakan sistem komputer spreadsheet. Metode pengabdian yang digunakan yaitu sosialisasi, pelatihan, dan pendampingan. Kegiatan dikemas dalam bentuk ceramah yang disampaikan secara virtual menggunakan zoom meeting dan Whats up Group (WAG). Khalayak sasarannya adalah pengurus dan Direktur BUMDes, serta perangkat Desa Jatijajar. Langkah yang ditempuh pertama adalah pelatihan input data transaksi pada sheet jurnal umum. Kedua yaitu praktik pencatatan dan posting pada buku besar umum dan pembantu sehingga menghasilkan laporan keuangan. Hasil kegiatan yaitu Direktur dan pengurus BUMDes paham dan mulai mengenal pencataan traksaksi keuangan dengan menggunakan SAK ETAP. Disamping itu juga mengenal rumus-rumus fungsi matematikan di dalam excel untuk menyusun spreadsheet general ledger akuntansi. General ledger tersebut mempermudah pencataan akuntansi dan penyusunan laporan keuangan yang disesuaikan dengan kebutuhan BUMDes. Jika BUMDes berbentuk perusahaan dagang, maka akan disusun laporan keuangan perusahaan dagang. Contohnya adalah minimarket dan toko kelontong yang dimiliki oleh BUMDes. Sedangkan jika perusahaannya adalah perusahaan jasa, maka disusun laporan keuangan perusahaan jasa yang disesuaikan dengan jenis jasa yang dijalankan. Semisal jasa pengelolaan air, jasa pengelolaan sampah, dan lainnya.